High-efficiency Doherty amplifier with metamaterial harmonic control for sub-6 GHz 5G base station - Faycal El Hardouzi; Mohammed Lahsaini (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2026)
This paper presents a broadband Doherty power amplifier (DPA) for Sub-6 GHz 5G wireless applications, integrating a metamaterial-based harmonic control circuit to suppress the 2nd and 3rd harmonics. The design employs a CGH40010F transistor on a Rogers RO3004C substrate. All results are obtained from simulations, while the resonator has been experimentally validated. The proposed approach enhances drain efficiency under output back-off (OBO) conditions without compromising linearity. Simulation results show a gain of 12.2–16.18 dB, with drain efficiency from 50.42 % to 79.83 %. Efficiency remains high at 3 dB and 6 dB back-off, ranging from 50.8–75.6 % and 36–62.8 %, respectively. These findings demonstrate the DPA’s potential for next-generation base stations requiring compact, efficient, and wideband amplifiers, offering a practical solution for modern wireless communication systems. The novelty lies in combining broadband DPA design with harmonic suppression via metamaterials, providing improved efficiency and spectral performance.